Further notes on Indian Langelurillus Próchniewicz, 1994 (Araneae: Salticidae), with the description of two new species - Sanap, Rajesh V.; Tripathi, Rishikesh; Caleb, John T.d.; Koli, Hemlata; Koli, Vijay Kumar; Intodia, Anjana; Thackeray, Tejas (Zootaxa, 2026)
We describe two new species, Langelurillus sahyadri Sanap, Tripathi, Thackeray & Caleb sp. nov. (♂♀) from Maharashtra and Langelurillus udaipurensis Tripathi, Sanap & Caleb sp. nov. (♂) from Rajasthan. Additionally, the previously unknown females of L. lacteus Sanap, Joglekar & Caleb, 2017 and L. onyx Caleb, Sanap, Joglekar & Prajapati, 2017 are described for the first time. Detailed morphological descriptions, illustrations, diagnostic comparisons of the studied species, and a distributional map for all Indian species are provided.